Outbreaks of Foodborne Disease Associated with Fruit and Vegetable Juices, 1922–2019 - Matthew Krug; Travis Chapin; Michelle Danyluk; Renee Goodrich-Schneider; Keith Schneider; Linda Harris; Randy Worobo (EDIS, 2020)
This document provides an overview of juice-related foodborne outbreaks between 1922-2019. This information is useful to juice processors to aid in the identification of pertinent microorganisms, and also reviews locations, venues of juice preparations, and severity of juice-associated outbreaks.